Women’s income generating activities and community disaster resilience: Evidence from Gaurichanna Union - Md. Faisal; Tamima Akhter Tanni; Tanvir Ahmed (Journal of Socio-Cultural Sustainability and Resilience, 2026)
Background: In Bangladesh especially in rural regions, women empowered through income generating activities (IGAs) and can enhance their capacity to cope with different disaster. Rural women are involved in different works in agricultural and non-agricultural sectors. The main aims of this study are to identify the existing income-generating activities (IGAs) of women in the study area; and to examine the role of women’s income-generating activities in community disaster resilience. Methods: The study was conducted at Gaurichanna Union in Barguna Upazila, Bangladesh. To conduct this research, data has been collected through individual questionnaire survey, focus group discussion, and life history from local people for fulfill the objectives. Findings: It has been found that the main income generating activities (IGAs) of the study area are, agricultural activities (homestead gardening, cattle and goat rearing, poultry rearing, worm composting, pond fish culture and fruit tree cultivation) and non-agricultural activities (tailoring, handicraft, rice/paddy husking, daily worker, street vendor and running small business). The results suggest that women’s participation in these activities contributes to improved household income, livelihood diversification, and enhanced capacity to cope with economic and environmental shocks. Conclusion: The study highlights that IGAs can support household livelihood security and contributes to strengthening resilience in disaster-prone coastal communities. These findings provide useful insights for policymakers and development organizations seeking to promote women’s economic participation and community resilience in vulnerable rural areas of Bangladesh. Novelty/Originality of this article: This study lies in linking rural women’s income-generating activities with household disaster resilience in a coastal hazard-prone context. By linking women’s economic participation with multiple dimensions of resilience, the research highlights the role of women’s livelihood strategies can strengthen adaptive capacity in vulnerable rural communities.